The place where you live and self-rated health in a large urban area - Rodrigues, Daiana Elias; César, Cibele Comini; Xavier, César Coelho; Caiaffa, Waleska Teixeira; Proietti, Fernando Augusto (Cadernos de saúde pública, 2015)
Abstract The aim of this study was to determine and quantify the association between one’s perception of the place of residence and self-rated health. 4,048 adult residents of Belo Horizonte, Minas Gerais State, Brazil, participated in the study in 2008 and 2009. Ordinal logistic regression was used to estimate the magnitude of the association. Health was rated as good or very good, fair, or poor or very poor by 65.7%, 27.8%, and 6.5% of the subjects, respectively. Better self-rated health was associated with the following neighborhood characteristics: positive evaluation of aesthetics and mobility, better quality of public services, less physical and social disorder. The perception of violence had a borderline statistically significant association with worse self-rated health. These associations persisted after controlling for potential confounding demographic, socioeconomic, health, and health behavior variables. The results indicate that public and health policies should incorporate interventions that address the physical and social environment in addition to policies focused on individuals. Resumen El objetivo de este estudio fue determinar la relación entre la percepción del lugar de residencia y la autopercepción de la salud. La información se obtuvo a través de entrevistas a 4.048 adultos que viven en Belo Horizonte, Minas Gerais, Brasil, entre 2008 y 2009. Para evaluar la asociación se utilizó la regresión logística ordinal. La autopercepción de la salud fue reportada como buena/muy buena, regular y mala/muy mala, respectivamente, por el 65,7%, 27,8% y 6,5% de los participantes. Una mejor autopercepción de la salud se asoció con los siguientes aspectos del vecindario: la evaluación positiva de la estética y de la movilidad, la mejora de la calidad de los servicios locales, menos desorden físico y social. La percepción local de violencia mostró asociación estadística marginal con una mala autopercepción de salud. Los resultados mantuvieron el control de posibles variables de confusión demográficas, socioeconómicas, condiciones y conductas de salud. Los resultados indican que las políticas públicas y de salud deben incorporar intervenciones sobre el entorno físico y social, además de sobre las políticas de corte individual. Resumo O objetivo deste estudo foi determinar e quantificar a associação entre autopercepção do local de moradia e autoavaliação da saúde. Participaram da pesquisa 4.048 adultos residentes em Belo Horizonte, Minas Gerais, Brasil, de 2008 a 2009. Para estimar a magnitude das associações foi utilizada regressão logística ordinal. Autoavaliação da saúde boa/muito boa, razoável e ruim/muito ruim foi relatada por 65,7%, 27,8% e 6,5% dos participantes, respectivamente. Melhor autoavaliação da saúde foi associada às seguintes características da vizinhança: avaliação positiva dos aspectos estéticos e da mobilidade, melhor qualidade dos serviços, menor desordem física e social. A percepção da violência apresentou associação estatística limítrofe com pior autoavaliação da saúde. As associações se mantiveram após o controle para potenciais variáveis de confusão demográficas, socioeconômicas, de condições de saúde e comportamentos em saúde. Os resultados indicam que políticas públicas e de saúde devem incorporar intervenções sobre o entorno físico e social em complemento às políticas individuais.